Liver and spleen of hosts of Rhipicephalus linnaei exposed to synthetic (afoxolaner) and natural acaricides (esters from castor oil). A comparative clinical-morphological study - Sodelli, Luís Fernando [UNESP]; da Silva, Odaiza [UNESP]; Araújo, Bruna Jéssyca Nascimento [UNESP]; Camargo-Mathias, Maria Izabel [UNESP] (FapUNIFESP (SciELO), 2023)
In dogs, Rhipicephalus linnaei transmits pathogens such as Ehrlichia canis, Babesia vogeli, and Hepatozoon canis. The veterinary market has synthetic acaricides to ticks control. Esters derived from castor oil are efficient. However, there is little information about their effects on non-target organisms. This work consisted of a clinical (AST, ALT, and ALP) and histological and histochemical analysis (liver and spleen) of female rabbits exposed to these esters and afoxolaner. The rabbits were divided into three groups: control group (CG) received Bandeirante® rabbit feed; the afoxolaner treatment (TG1) received rabbit feed and two doses of afoxolaner; castor oil esters treatment (TG2) received rabbit feed enriched with esters (1.75 g esters/kg). No alterations were observed in the AST, ALT, and ALP enzymes in exposure to esters TG2. Rabbits from TG1 showed changes in AST. The liver of rabbits exposed to afoxolaner underwent histological and histochemical changes, such as steatosis and vacuolation, as well as poor protein labeling. Polysaccharides were intensely observed in the group exposed to esters. The spleen showed no changes in any of the exposure. Esters from castor oil caused fewer liver changes when incorporated into the feed and fed to rabbits than exposure to afoxolaner.
Fígado e baço de hospedeiros de Rhipicephalus linnaei expostos aos acaricidas sintético (afoxolaner) e natural (ésteres do óleo de mamona). Estudo clínico-morfológico comparativo
Keywords: Brown dog tick; isoxazoline; natural product; Nexgard®; Ricinus communis